Seroxat and the suppression of clinical trial data: regulatory failure and the uses of legal ambiguity - McGoey, L; Jackson, E (2008)
This article critically evaluates the Medicines and Healthcare products Regulatory Agency’s announcement, in March 2008, that GlaxoSmithKline would not face prosecution for deliberately withholding trial data, which revealed not only that Seroxat was ineffective at treating childhood depression but also that it increased the risk of suicidal behaviour in this patient group. The decision not to prosecute followed a four and a half year investigation and was taken on the grounds that the law at the relevant time was insufficiently clear. This article assesses the existence of significant gaps in the duty of candour which had been assumed to exist between drugs companies and the regulator, and reflects upon what this episode tells us about the robustness, or otherwise, of the UK’s regulation of medicines.